2022
DOI: 10.1002/cey2.220
|View full text |Cite
|
Sign up to set email alerts
|

Engineering homotype heterojunctions in hard carbon to induce stable solid electrolyte interfaces for sodium‐ion batteries

Abstract: Developing effective strategies to improve the initial Coulombic efficiency (ICE) and cycling stability of hard carbon (HC) anodes for sodium-ion batteries is the key to promoting the commercial application of HC. In this paper, homotype heterojunctions are designed on HC to induce the generation of stable solid electrolyte interfaces, which can effectively increase the ICE of HC from 64.7% to 81.1%. The results show that using a simple surface engineering strategy to construct a homotypic amorphous Al 2 O 3 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…In comparison with the reported sodium‐ion anodes (FeNx@C, FeP@NC, Bi 2 Te 3 @ppy, TiNbO 5 @rGO, etc. ), [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] the 1T’ Re 0.75 V 0.25 Se 2 electrode has very big advantages in ultra‐high rate capacity and long‐term cycling stability (Figure 3g ).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the reported sodium‐ion anodes (FeNx@C, FeP@NC, Bi 2 Te 3 @ppy, TiNbO 5 @rGO, etc. ), [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] the 1T’ Re 0.75 V 0.25 Se 2 electrode has very big advantages in ultra‐high rate capacity and long‐term cycling stability (Figure 3g ).…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20] Thereinto, polyanionic compounds have attracted much attention due to their framework structure, structural stability and high workingpotential with the potential for high energy density, such as Na 3 MnPO 4 CO 3 , Na 2 MnP 2 O 7 and Na 4 Mn 3 (PO 4 ) 2 P 2 O 7 . [21][22][23][24][25][26] In…”
Section: Introductionmentioning
confidence: 99%
“…15–20 Thereinto, polyanionic compounds have attracted much attention due to their framework structure, structural stability and high working-potential with the potential for high energy density, such as Na 3 MnPO 4 CO 3 , Na 2 MnP 2 O 7 and Na 4 Mn 3 (PO 4 ) 2 P 2 O 7 . 21–26 In particular, metal-based mixed phosphates provide a higher potential originating from the stronger inductive effect of large-sized (PO 4 )(P 2 O 7 ) groups, multiple Na + insertion/extraction sites and three-dimensional open channels. 27–29 So far, the recent developments on mixed phosphates cathode materials have been widely reviewed by some research groups.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ALD coatings enhance the shelf life, capacity, and energy density of these batteries. ALD is used to form nanoscale artificial solid electrolyte interfaces (SEI) at the anode and to form protective thin film coatings on cathode electrode materials, to enhance cycling stability, and to prevent degradation of the electrolyte and electrode material. For example, ALD Al 2 O 3 is widely used as an artificial SEI material on hard carbon or graphitized anodes in sodium-ion and lithium-ion batteries. However, the success of ALD aluminum oxide as a protective coating in battery applications is varied. In some instances, ALD aluminum oxide has been described to react with the electrolyte, generating phases with high Li-ion conductivity. , In other instances, thicker nanoscale films of ALD aluminum oxide have been found to exhibit low Li-ion conductivity and limit the charge rate of lithium-ion batteries .…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl-terminated CNTs employed here are a convenient low-Z substrate with a cylindrical sample geometry allowing us to localize the electron beam at various points along the cross section of the ALD coating. Furthermore, understanding the local atomic structure of ALD aluminum oxide grown on sp 2 carbon substrates like CNTs is relevant to understand the behavior of ALD protective coatings on graphitic and carbon electrode materials in lithium-ion and sodium-ion batteries. Scanning transmission electron (STEM) microprobe mode was used to obtain a small (∼5 nm) focused beam and allowed us to localize the beam on the AlO x coating without the contribution of the CNT substrate. Here, we establish the atomic structure of ALD-AlO x as a function of the position through the depth of the ALD coating.…”
Section: Introductionmentioning
confidence: 99%